Perfil dos produtores de arroz irrigado da fronteira oeste do RS, ligados a Pirahy Alimentos - Bonetti, Alberto dos Santos (2007)
The present work had how I aim to obtain informations on current situation of producers irrigated rice (orizum sativum l.), suppliers-partners of the Agroindústria Pirahy Food, in Saint western Borja-frontier of the Rio Grande do Sul, carried out through pesquiza carried out with producers of irrigated rice located in the local authorities of Saint Borja, Itaqui, Bed, in the western frontier of the Rio Grande do Sul, harvest 2006-2007. These informations were analysed as for productivity, use of the land, area of cultivation, access, system of cultivation, dimenssion machines, type of sowing, equipment of pulverizizacao, it plots of harvest, type, dimenssion and of energy of the system of irrigation, system of evaluation of the of the fertility and correction of the acidity of the ground, use, use, you cultivate, density and time of sowing, realization of Integrated Handling of Nuisances, control of nuisances and diseases, time of harvest, I handle powders-harvests, drying and storage, and realization and control of costs of production and realization of qualification of colabroradores in the lavouras. They allowed the obtained results to end that the middle productivity from 7 to 8 tons per hectare; 66 % of the producers uses leased lands and or partnerships; 84 % of the producers cultivates even 400ha; 88 % of the producers happens least cultivation and in 9 % they associate the least cultivation to a conventional one; the access roads of 80 % of the producers it has easy access itself when haste is taking place in the harvest time; 72 % carries out the dimensionamentos of machines in accordance with the area of cultivation; 98 % uses machines of movement and preparation of the ground, 87 % of the producers uses sowing in line; the totality they used land equipment and he was seeing 76 % carries out repression of the water of irrigation; they used techniques of dimension of the system of irrigation; 78 % used only electric energy as energetic fountain of the system of irrigation; 87 % carries out analysis of ground for each productive cycle; 71 % carries out analysis and correction of the ground for each productive cycle; 82 % when 13 % was supervised, 5 % registered, basic. In Bed 100 % of the producers uses certified seeds; 89 % carries out analysis of germination and energy of seeds for each productive cycle; 40 % to cultivate BRIrga 409 and 8 % BRIrga 409 and 14 % uses others you cultivate; 93 % of the producers carries out the sowing in October and November; 84 % does not carry out MIP; 41 % carries out the control of nuisances in powders-emergences the remainder in daily pay and powdersemergences; 21 % uses the cultural and chemical control of diseases and the remainder uses only chemical control; 87 % carries out control in the maturing of Field or after the maturing of field; 100 % carries out handling powders-harvests in the property or in in third; 25 intermittent % and 14%silos, the remainder uses handling powders-harvests in third; 41 % carries out handling powders-harvests in the property uses brick warehouses, the wooden remainder or mixture; 77 % carries out the control of costs in the rural property; 91 % of the producers of irrigated rice carries out courses of training, qualification and requalificacao for the owner and collaborators.